Effect of melatonin treatment on growth characteristics of tobacco (Prilep) plants under PEG artificial drought stress conditions (Journal of Hama University, 2025)
In this work, we studied the effect of treatment with melatonin at concentrations (50, 100 and 150 microliters) on some biochemical and production characteristics of Prilep tobacco plants under conditions of applied drought stress (15, 30 and 45%).Plant height, total leaf surface area, and leaf area index decreased under conditions of drought stress, and the net photosynthesis rate and specific gravity decreased steadily with increasing applied stress, while all studied indicators increased when sprayed with melatonin, especially at low concentrations.The treatment with the reduced concentration of melatonin and the applied stress outperformed all treatments and the control for all indicators studied.Therefore, it is recommended to use melatonin, especially at a concentration of 50 microliters, on tobacco plants because of its role in improving growth and morphological characteristics under conditions of drought stress.
Keywords: Tobacco seeds; Prilep; melatonin; drought stress